Revisiting Sustainable Food Agriculture Land Protection Policy: Lesson from Gunungkidul, Indonesia - Anggalini, Titis Dewi (UIN Sunan Ampel Surabaya, 2024)
Climate change will have a negative impact on farmers due to changes in rainfall, air temperature, and water availability, especially in drought prone areas such as the Gunungkidul regency of Indonesia. This may disrupt food availability, because it forces farmers to switch the function of agricultural land, especially paddy fields, to more commercially productive uses. The Sustainable Food Agriculture Land Protection (SFALP) Policy is a policy designed to suppress the conversion of land functions so that food availability remains stable and even increases in the future. This research aims to understand the overall performance conditions of the SFALP policy implementation, constraints, and supports for the policy. The research is qualitative, with a case study approach. Data are collected qualitatively through literature study, observation, in-depth interview and focus group discussion. In terms of policy input, the availability of financial and human resources is sufficient because currently the main focus is on planning and designation activities, but the availability of land with new rules is insufficient, so there must be new rice fields planted. In terms of output, there is no established Sustainable Food Agriculture Area (SFAA), but there are some indications of one. Barriers include unclear policy incentives, policies that are logically inaccurate in determining SFAA, the limited budget, attracting public interest, weak juridical enforcement due to unclear regulations, and overlapping inter-organizational relations. Support comes from farmers' receipts, the existence of local regulations on SFALP in Gunungkidul Regency, and support from the Gunungkidul Regent and the Provincial Government.